The redesign of the careers and their challenges for the teachers of Quevedo State Technical University, Ecuador - Pérez Cruz, Isabel (2017)
The process of renewal of Ecuadorian universities is based on a new epistemic paradigm and has, among its challenges, the permanent improvement of teachers’ training. The general objective of the research is to evaluate the challenges that the process of program design and redesign represents for UTEQ professors’ staff, in order to systematize their continuous training, based on science and pedagogy, in accordance with the demands of the Ministry of Higher Education in Ecuador for the epistemology based formation of teachers. From the conception of participatory action research, workshops encouraging reflection and participation of teachers and researchers were held. The main results obtained were: active participation of teachers in results related to the improvement of, knowledge, pedagogical, investigative and technological training, as well as the socialization of the epistemological horizons of UTEQ undergraduate programs and the development of professional competences of the teachers’ staff